2022
DOI: 10.3389/fnut.2022.1015371
|View full text |Cite
|
Sign up to set email alerts
|

High dietary non-starch polysaccharides detrimental to nutrient digestibility, digestive enzyme activity, growth performance, and intestinal morphology in largemouth bass, Micropterus salmoides

Abstract: An 8-weeks feeding trial was carried out to evaluate the effects of different levels of dietary non-starch polysaccharide on the growth, apparent nutrient digestibility, intestinal development, and morphology of largemouth bass (Micropterus salmoides). Seven isoproteic and isolipidic experimental diets were formulated (crude protein 47.00%, crude lipid 12.50%), containing 0, 3, 6, 9, 12, 15, and 18% non-starch polysaccharides (NSPs) (named Control, NSPs3, NSPs6, NSPs9, NSPs12, NSPs15, and NSPs18), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…However, a significant positive correlation was found between fish growth and ADC CP . Similar results were found in largemouth bass (M. salmoides) [39]. It was also found that ADC CP was closely related to ADC TEAA .…”
Section: Discussionsupporting
confidence: 83%
“…However, a significant positive correlation was found between fish growth and ADC CP . Similar results were found in largemouth bass (M. salmoides) [39]. It was also found that ADC CP was closely related to ADC TEAA .…”
Section: Discussionsupporting
confidence: 83%
“…Liu et al showed that increased viscosity of chyme could reduce the growth performance of largemouth bass and cause in ammation (Liu et al, 2022). Other researchers found that high chyme viscosity would damage intestinal morphology and reduce nutrient absorption in largemouth bass (Liu et al, 2022b, Liu et al, 2022a. Therefore, excessive addition of YPP may lead to an increase in PEC and chyme viscosity, ultimately leading to damage to the intestinal health of largemouth bass.…”
Section: Discussionmentioning
confidence: 99%
“…The hindgut intestines were immersed in 10% neutral formalin for 24 h and subsequently underwent dehydration, embedding, sectioning, and spreading following the standard procedures described by Liu et al. (2022) .…”
Section: Methodsmentioning
confidence: 99%